The Role of the Police in Efforts to Prevent and Overcome Child Sexual Violence in Bangkalan Regency (Study on Bangkalan Police) - wijaya, nico agus; Hidayat, Nur Azizah (Academos, 2022)
AbstractSexual crimes do not only happen to adults, often the victims are minors. The prevalence of this crime in the community is evidenced by data obtained by researchers at the Bangkalan Resort Police (Bangkalan Police), which shows an increase every year. This study aims to determine the role of the Bangkalan Police. This research is a non-doctrinal legal research with a legal sociology approach. The results of this study indicate that the Bangkalan Police have provided education to the public about the dangers of sexual violence against children and their prevention measures, as a preventive measure. In addition, the curative efforts carried out by the Bangkalan Police are to process perpetrators of sexual violence against minors seriously so that can be proven and prosecuted the maximum sentenceKeywords: The Role of The Police; Sexual Violence; Child